LITERATURE REVIEW ETNOBOTANI: POLA PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT ADAT - Syalsa Nadya Zahara; Reki Kardiman (JURNAL BIOSENSE, 2026)
The use of medicinal plants by indigenous people is a form of local wisdom that is still preserved today. Indonesia's high biodiversity contributes to the development of traditional knowledge in the use of plants as natural remedies. This review article aims to analyze patterns of medicinal plant use by indigenous people, identify the most commonly used plant species, and understand how they are processed and utilized in traditional medicine. The method used was a literature review of various national and international scientific articles obtained through Google Scholar and ScienceDirect using the keywords "ethnobotany of medicinal plants," "use of medicinal plants by indigenous peoples," and "medicinal plant ethnobotany."The review results indicate that indigenous peoples utilize various types of medicinal plants found in their yards, gardens, and forests. The most commonly used plant part is the leaf, while the dominant processing methods include boiling, pounding, and direct application. Medicinal plants are generally used to treat ailments such as fever, diarrhea, hypertension, coughs, digestive disorders, and skin diseases.Based on the analysis, it is clear that the use of medicinal plants not only plays a role in maintaining public health but also reflects the relationship of local culture and knowledge to the environment. Therefore, efforts are needed to document, preserve, and develop ethnobotanical research so that traditional knowledge regarding medicinal plants is maintained and can be utilized sustainably.